2019
DOI: 10.1182/blood.2019000800
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 PIG-A gene editing in nonhuman primate model demonstrates no intrinsic clonal expansion of PNH HSPCs

Abstract: Recent advances in gene editing technologies using CRISPR/ Cas9 allow precise genome editing at a site of interest and have accelerated human disease modeling and the development of corrective gene therapies for various genetic disorders. 1,2 We adapted CRISPR/Cas9 editing of rhesus macaque (RM) hematopoietic stem and progenitor cells (HSPCs) to create the first engineered large animal model of a hematologic disease based on close phylogenetic/functional similarity of RM to human HSPCs. 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…Granulocytes turn over every several days and thus reflect ongoing production from HSPCs. Sites ZJ52-CS1/ISP7, ZJ52-CS3/ISP8 and ZJ52-CS25/ISP1 with bona fide indels detected in the IP also had convincing indel patterns in the granulocyte samples from the transplanted macaque, with higher indel percentages at 1 month compared to 5 months, a similar pattern observed for the on target site in this animal and others transplanted in our program, reflecting more efficient editing of short-term as compared to long-term engrafting HSPCs 5,23 . Sites ZJ52-CS9/ISP1258 and ZJ52-CS13 again had mutations not typical for Cas9-mediated editing, and did not change between 1 and 5 months, further suggesting that these two sites were not actually edited but instead were sites prone to sequencing errors (Table 1).…”
Section: Results: Identification and Comparison Of Off-target Sites Psupporting
confidence: 82%
“…Granulocytes turn over every several days and thus reflect ongoing production from HSPCs. Sites ZJ52-CS1/ISP7, ZJ52-CS3/ISP8 and ZJ52-CS25/ISP1 with bona fide indels detected in the IP also had convincing indel patterns in the granulocyte samples from the transplanted macaque, with higher indel percentages at 1 month compared to 5 months, a similar pattern observed for the on target site in this animal and others transplanted in our program, reflecting more efficient editing of short-term as compared to long-term engrafting HSPCs 5,23 . Sites ZJ52-CS9/ISP1258 and ZJ52-CS13 again had mutations not typical for Cas9-mediated editing, and did not change between 1 and 5 months, further suggesting that these two sites were not actually edited but instead were sites prone to sequencing errors (Table 1).…”
Section: Results: Identification and Comparison Of Off-target Sites Psupporting
confidence: 82%
“…FLAER detection of granulocytes, monocytes, and lymphocytes in the PNH rhesus macaque model, permitted the dynamic monitoring of changes in PNH cloning in rhesus macaques. The results showed that abnormal PNH clones in rhesus macaques equally had no proliferation advantage [26], consistent with results from the PNH mouse model.…”
Section: Evaluation and Existing Problems Of Pnh Animal Modelssupporting
confidence: 84%
“…Tae-hoon Shin successfully constructed PNH rhesus macaque models of PIG-A gene KO in hematopoietic stem cells through CRISPR/Cas9 gene editing [26]. The CRISPR/Cas9 system is made up of the CRISPR gene and the Cas9 endonuclease.…”
Section: Pig-a Gene Knockout Rhesus Macaque Modelmentioning
confidence: 99%
“…However, no PNH clones and proliferation have been found, and no clinical symptoms of PNH 14 . In Shin TH et al 2019, the data gathered about PNH macaque model using CRISPR/Cas9 technology to create model of hematologic disease based on the near phylogenetic/functional similarity between macaque and human was shown that there was no intrinsic clonal ampli cation of PNH-HSPCs 15 . At present, studies reported that immune-escape characteristics 16 17 18 , anti-apoptotic properties 19 20 , and second gene mutations 21 22 23 may be involved in the ampli cation of PNH clones.…”
Section: Discussionmentioning
confidence: 99%